Camelot - Logan, Joshua L. (Warner Home Video, 2001)
The legend of King Arthur has enchanted generation after generation. His pure perfect kingdom was shattered because of the tragic passion between Queen Guenevere and the Round Table's bravest knight Lancelot. Alan Jay Lerner and Frederick Loewe (My Fair Lady, Brigadoon) Fashioned that legend (From T.H. White's book The Once In Furture King) into the 1960 Broadway musical Camelot, Seven years later, the stage hit became movie history, a visually splended triple Academy Award winner with glowing performances by Richard Harris, Vanessa Redgrave and Franco Nero and a glistening score; If Ever I Would Leave You, the title tune, How To Handle A Woman and other beloved songs. For its 30th anniversary, this digitally remastered vision delivers a revitalized picture and restored the intended sound mix from the original music recording sessions and dolby Digital Surround Experience anew the melodies, tye emotions, the rapture of "that one brief shining moment that was known as Camelot."